1996
DOI: 10.1046/j.1365-2362.1996.2350584.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of insulin on cholesterol removal from macrophages and cholesterol ester uptake by HepG2 cells

Abstract: The fact that an increased blood insulin level is observed in patients with coronary artery disease (CAD) confirms the hypothesis that insulin promotes the development of atherosclerosis. The low high-density lipoprotein (HDL) concentration observed in such patients may contribute to alteration in reverse cholesterol transport and promote the accumulation of sterols in vascular tissue. We examined the effect of insulin (20-1000 microU mL-1) on cholesterol efflux into HDL3 particles from human blood monocyte/ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…39,40 In our study, we demonstrated that insulin inhibited cholesterol synthesis in peritoneal macrophages in a dose-dependent manner, both in the ex vivo and in the in vitro studies. Thus, the reduced macrophage cholesterol content in insulin supplemented mice may be attributable to the inhibition of cholesterol synthesis induced by insulin.…”
Section: Shamir Et Almentioning
confidence: 54%
“…39,40 In our study, we demonstrated that insulin inhibited cholesterol synthesis in peritoneal macrophages in a dose-dependent manner, both in the ex vivo and in the in vitro studies. Thus, the reduced macrophage cholesterol content in insulin supplemented mice may be attributable to the inhibition of cholesterol synthesis induced by insulin.…”
Section: Shamir Et Almentioning
confidence: 54%
“…The effects of insulin on reverse cholesterol transport are incompletely understood. Insulin may inhibit cellular cholesterol efflux in vitro [17,18], as well as cholesterol uptake in hepatic cells, either directly [18] or by lowering hepatic lipase activity [19]. Little is known about the effects of insulin on plasma cholesterol esterification and (CET).…”
Section: Introductionmentioning
confidence: 99%
“…HDL plays a pivotal role in cholesterol efflux, which is the initial step of reverse cholesterol transport (RCT) 26) ; however, the distinct mechanism of impaired RCT in type 2 diabetes is not well understood. Insulin has been reported to counteract cholesterol removal from human macrophages 23,27) and skin fibroblasts 28) , although the precise mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%